2019
DOI: 10.1111/desc.12910
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term numerosity training promotes symbolic arithmetic in children with developmental dyscalculia: The mediating role of visual form perception

Abstract: Studies have shown that numerosity‐based arithmetic training can promote arithmetic learning in typically developing children as well as children with developmental dyscalculia (DD), but the cognitive mechanism underlying this training effect remains unclear. The main aim of the current study was to examine the role of visual form perception in arithmetic improvement through an 8‐day numerosity training for DD children. Eighty DD children were selected from four Chinese primary schools. They were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…It plays a role in spatial navigation, mnemonic processing, and control of the response to emotional stress. In fact, it has been shown that DD demonstrate problems with spatial navigation and spatial processing (e.g., visual crowing: identifying objects when surrounded by other simular items) related to memory and inhibition (Castaldi et al., 2020; Szucs et al., 2013), which appear to be still present after numerosity‐based arithmetic training (Cheng et al., 2020). From our results and based on the recorded behavioral data, we cannot comment on why the subiculum shows lower SC in DD.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in spatial navigation, mnemonic processing, and control of the response to emotional stress. In fact, it has been shown that DD demonstrate problems with spatial navigation and spatial processing (e.g., visual crowing: identifying objects when surrounded by other simular items) related to memory and inhibition (Castaldi et al., 2020; Szucs et al., 2013), which appear to be still present after numerosity‐based arithmetic training (Cheng et al., 2020). From our results and based on the recorded behavioral data, we cannot comment on why the subiculum shows lower SC in DD.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in recent years, approaches for remediation have been developed to enhance numerical cognition, for example, computer-assisted interventions (Kucian et al, 2011;Syah et al, 2015;Michels et al, 2018;Cheng et al, 2019), board games (Elofsson et al, 2016), and tutoring programs, i.e., the combination of conceptual features of numerical knowledge with counting skills (Iuculano et al, 2015), and even attentional training (Ashkenazi and Henik, 2012). These interventions produced improvements in the numerical cognition capacity, however, the effect was restricted to isolated numerical abilities such as number sense (Wilson et al, 2006), number line (Kucian et al, 2011;Käser et al, 2013;Elofsson et al, 2016), or number comprehension (Fuchs et al, 2013;Syah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a domain‐general hypothesis provides an alternative explanation for the association between numerosity processing and arithmetic fluency from the viewpoint of general cognitive processing. Visual perception, as measured by a geometric figure‐matching task, has emerged as a critical general cognitive mechanism that is shared between non‐verbal number sense and arithmetic fluency (Cheng et al, 2020; Cui, Zhang, Cheng, Li, & Zhou, 2017; Wang, Sun, & Zhou, 2016; Zhou, Hu, Yuan, Gu, & Li, 2020; Zhou, Wei, Zhang, Cui, & Chen, 2015). For example, Zhou et al (2015) showed that visual perception measured with such a task could fully account for the association between non‐verbal number sense and arithmetic fluency.…”
Section: Introductionmentioning
confidence: 99%